'Gas-dynamic diode': Streamer interaction with sharp density gradients. (24th September 2019) - Starikovskiy, A Yu; Aleksandrov, N L
Abstract: The conditions were found when the gaseous medium demonstrates a unidirectional conductivity on a short time scale; a gas density discontinuity forms a kind of 'gas-dynamic diode' that allows the plasma channel to propagate in one direction and blocks its development in another. The results of a two-dimensional numerical simulation of a streamer discharge developing through a shock wave in air are presented for various neutral density discontinuities across the wave. The focus was on the case when the streamer propagated from a low-density region to a high-density region. Streamer characteristics changed greatly after intersecting the shock wave. It was shown that the streamer failed to penetrate into the high-density region when the ratio between the densities in these regions was sufficiently high (>1.2). In this case, the discharge developed along the surface between these regions after reaching the boundary between them. Streamers could penetrate into any of the high-density and low-density regions when a neutral particle density discontinuity was replaced by a gradual density change.